The music never stopped - Noll, Julie W.; Lurie, Gwyn.; Marks, Gary.; Kohlberg, Jim.; Cantelon, Paul.; Reamer, Keith; Kazmierski, Steve; Sacks, Oliver W.; Simmons, J. K.; Pucci, Lou Taylor, 1985-; Seymour, Cara.; Ormond, Julia; et al. (Santa Monica, Calif. : Lions Gate Films, 2011)
Historia de un padre que lucha por un vínculo con su distanciado hijo Gabriel, después de que Gabriel sufre de un tumor cerebral que le impide la formación de nuevos recuerdos.
En inglés con subtítulos en español.
Based on the essay "The last hippie" by Oliver Sacks.
Music, Paul Cantelon ; editor, Keith Reamer ; director of photography, Steve Kazmierski.
J. K. Simmons, Lou Taylor Pucci, Cara Seymour, Julia Ormond.
DVD ; widescreen (2.35:1) presentation ; Dolby digital 5.1surround.
MPAA rating: PG; for thematic elements, some mild drug references, language and smoking.
Keywords: Padres e hijos -- Drama; Cerebro -- Cáncer; Música rock -- 1961-1970.; Películas cinematográficas